FOREIGN PRIVATE PARTICIPATION FOR THE PROVISION OF STRATEGIC INFRASTRUCTURE IN INDONESIA: A LEGAL PERSPECTIVE - Trisnamansyah, Purnama; Adolf, Huala; Rosadi, Sinta Dewi; Sudirman, Arfin; Maulana, Mursal (CENTRAL ASIA AND THE CAUCASUS, 2024)
Infrastructure is seen as an essential and significant element of competitiveness, in driving the national economy. The government continues to pursue advanced infrastructure development to improve Indonesia's competitiveness ranking at the international level through National Strategic Project (NSP). Previously, the financing for the provision of national infrastructure was highly dependent on the funding by the government. The government’s funding, was limited in number, so that it was not sufficient to meet the financing needs of national infrastructure. Its development began a paradigm shift that in financing the provision of infrastructure, it no longer relied solely on government’s budget but also provided opportunities for foreign private companies to invest in the required infrastructure projects. This new paradigm reflects the spirit of "not doing business as usual" in financing infrastructure provision in Indonesia. In the national economy based on economic democracy, both national and foreign private firms can develop the Indonesian economy. Foreign private investment in financing the provision of strategic infrastructure is included in production branches that are important to the state and control many people's livelihoods. It is realized through a partnership between foreign private companies and State-Owned Enterprises (SOEs). The cooperation is built on the condition that foreign partner is needed. The SOEs invite them to participate in the provision of strategic infrastructure while still placing the state firms as the determinant actor in decision-making and the holder of control in the management of the national strategic infrastructure. However, in providing opportunities for foreign private companies in delivering national strategic infrastructure, an analysis of the costs and benefits should be carried out so that the benefits obtained would be more significant than the costs borne by the Indonesians to improve their welfare.